1994
DOI: 10.1111/j.1365-2141.1994.tb04878.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antithrombin deficiency in the healthy population

Abstract: In a cohort of 9669 blood donors we have identified 16 cases of congenital AT deficiency (1 in 600) by way of family studies and AT gene analysis. Two donors had type I AT deficiency (prevalence 0.21 per 1000; 95% CI = 0.03/1000 to 0.75/1000), their families displaying a symptomatic phenotype. 14 donors had a type II deficiency (prevalence 1.45 per 1000; 95% CI = 0.79/1000 to 2.43/1000): one recurring and three unique mutations. None of these type II deficiencies appeared to confer a high thrombotic risk despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
222
2
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(242 citation statements)
references
References 26 publications
9
222
2
9
Order By: Relevance
“…This compound heterozygous patient, who had a R147W mutation and a one-base deletion causing a frameshift followed by an early termination, first developed DVT at the age of 24 years. The same R147W mutation was reported later by Tait et al in an asymptomatic kin [16]. Now, we found that it was the most common genetic defect in symptomatic patients with protein C deficiency in Taiwanese Chinese.…”
Section: Discussionsupporting
confidence: 88%
“…This compound heterozygous patient, who had a R147W mutation and a one-base deletion causing a frameshift followed by an early termination, first developed DVT at the age of 24 years. The same R147W mutation was reported later by Tait et al in an asymptomatic kin [16]. Now, we found that it was the most common genetic defect in symptomatic patients with protein C deficiency in Taiwanese Chinese.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of heterozygous protein C deficiency is estimated to be one in 200 to 300, or 500 of the general Western population (23,24). In Japan, it is reported to be one in 620 (25).…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygosity for protein C deficiency is inherited in an autosomal dominant fashion and affects between 0.2% -0.5% of the population [54] [55]. However, there is a lot of variation in phenotype and many carriers will be asymptomatic.…”
Section: Protein C Deficiencymentioning
confidence: 99%
“…In another population-based cohort study examining VTE risk among women with PCOS who were not using hormonal contraception the relative risk of VTE compared to non PCOS subjects was 1. 55 …”
Section: Polycystic Ovary Syndromementioning
confidence: 99%